Damages of aviation constructions made of composite materials - Горобец, П. И.; Хоменко, A. B.; Шевченко, O. A. (Proceedings of National Aviation University (archive), 2000)
Considered are the causes and character of development of damages typical for majority of composite plastic materials compared to those made of metals. Made is classification of damages caused by mechanical impact to polymer composite materials according to energetic and velocity principle. Presented are constructive solutions for units made of polymer composite materials resistant to mechanical impacts